Some dynamical calculations of a transducer of two constact points type with two degrees of freedom - Hung, Do Trong; Khang, Nguyen Van; Sanh, Do; Tho, Banh Xuan; Tho, Ho Dac (Vietnam Journal of Mechanics, 1982)
As it is known, in machine-building two methods are used for checking the size of manufacturing details: the method of active check and the method of passive check and in connection with this there are two checking remedies: that of active check and passive check Is discussed in this paper the dynamical calculation of a transducer of type of two constact points with two degrees of freedom. The obtained results have been used for calculating a transducer for the national ·program 52.01.